2023
DOI: 10.1007/s11682-023-00793-3
|View full text |Cite
|
Sign up to set email alerts
|

Voxel-based morphometry of grey matter structures in Parkinson’s Disease with wearing-off

Heng Zhai,
Wenliang Fan,
Yan Xiao
et al.

Abstract: Our study aimed to investigate the grey matter (GM) changes using voxel-based morphometry (VBM) in Parkinson’s disease (PD) patients with wearing-off (WO). 3D-T1-weighted imaging was performed on 48 PD patients without wearing-off (PD-nWO), 39 PD patients with wearing-off (PD-WO) and 47 age and sex-matched healthy controls (HCs). 3D structural images were analyzed by VBM procedure with Statistical Parametric Mapping (SPM12) to detect grey matter volume. Widespread areas of grey matter changes were found in pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 52 publications
(60 reference statements)
1
1
0
Order By: Relevance
“…28,29 The technique's sensitivity to subtle and diffuse structural alterations is pivotal in delineating the neurodegenerative trajectory of such conditions. 30 Although our study was constrained by a modest sample size, the observed GMV changes in the FG and ITG are noteworthy and consistent with the anticipated neuroanatomical patterns in A-PD. It is important to acknowledge the intrinsic limitations of VBM, which include a lack of discernment between cortical thinning and alterations in surface area, as well as an absence of assessment regarding WM integrity.…”
Section: Advantages and Limitations Of Vbm In Pd Assessmentsupporting
confidence: 78%
“…28,29 The technique's sensitivity to subtle and diffuse structural alterations is pivotal in delineating the neurodegenerative trajectory of such conditions. 30 Although our study was constrained by a modest sample size, the observed GMV changes in the FG and ITG are noteworthy and consistent with the anticipated neuroanatomical patterns in A-PD. It is important to acknowledge the intrinsic limitations of VBM, which include a lack of discernment between cortical thinning and alterations in surface area, as well as an absence of assessment regarding WM integrity.…”
Section: Advantages and Limitations Of Vbm In Pd Assessmentsupporting
confidence: 78%
“…Asymmetry Voxel-Based Morphometry (VBM) allows for the calculation of the asymmetry index (AI), which quantifies the asymmetry in gray matter volume between the hemispheres. 21 Although numerous studies using VBM have identified gray matter volume reduction in PD, [22][23][24] research into the asymmetry of gray matter volume between the cerebral hemispheres in PD remains limited.…”
Section: Introductionmentioning
confidence: 99%